The environmental protection through utilising sustainable material in construction industry - Teo, Tze Meng (2013)
The environment impacts from the construction industry activities had lead to a growing realization that there is a need for a more sustainable approach to the construction industry. In Malaysia, the issues of environmental dissatisfaction on construction projects have regularly appeared in newspaper headlines. Hence, this research was carried out in order to investigate the environmental protection through utilising sustainable materials towards achieving sustainable development in construction industry. The implementation of sustainable development is crucial to the need for better environmental protection, economic prosperity, and social well-being. It can be achieved by execution of sustainable construction which can reduce environmental impact of a building over its entire lifetime while optimize economic viability and the comfort and safety of occupants. This research utilised quantitative research methodology where questionnaires were distributed among construction parties. The data collected through questionnaires was analyzed with Microsoft Excel and SPSS 16.0. The findings revealed that construction activities have significant effects on the environment which resulting air pollution, land pollution, noise pollution, water pollution, and waste pollution. Besides, results also shown that the respondents are aware on the sustainable issues in Malaysian construction industry. In short, the aluminum was selected as the most appropriate sustainable building material in the implementation of sustainable development in Malaysian construction industry.